Problems and Dispute Resolution of Hongkong Market Development and Management Cooperation - Novi Juli Rosani Zulkarnain (IHSA Institute, 2021)
Problem and Dispute Resolution of Hongkong Market Development and Management Coopertaion.Contract arrangements for places of business in the context of developing and managing the Hong Kong Market, when viewed from Article 1320 of the Civil Code, do not meet the first requirement, namely an agreement which is a subjective requirement. Because there is an element of error (dwaling, mistake). Because the authority of the Board of Directors based on the laws and regulations can make and sign contracts. Therefore, the contract can be canceled by referring to Articles 1266 and 1267 of the Civil Code, namely the cancellation is requested through a judge and the losses incurred as a result of the cancellation are calculated.The authority of PD.Pasar Kota Medan in making cooperation contracts has been fully granted by the legislation, the legal aspects that are the basis for the establishment of PD. Medan City Market, namely Law Number 5 of 1962 concerning Regional Enterprises, Law Number 32 of 2004 concerning Regional Government, Ministry of Home Affairs Number 50 of 1999 concerning BUMD Management.